Effect of fatigue on the intra-cycle acceleration in front crawl swimming: A time-frequency analysis - Tella, V.; Toca-Herrera, J. L.; Gallach, J. E.; Benavent, J.; Gonzalez, L. M.; Arellano, R. (Journal of Biomechanics, 2008)
The present study analyzes the changes in acceleration produced by swimmers before and after fatiguing effort. The subjects (n=15) performed a 25-m crawl series at maximum speed without fatigue, and a second series with fatigue. The data were registered with a synchronized system that consisted of a position transducer (1 kHz) and a video photogrametry (50 Hz). The acceleration (m s-2) was obtained by the derivative analysis of the variation of the position with time. The amplitude in the time domain was calculated with the root mean square (RMS); while the peak power (PP), the peak power frequency (PPF) and the spectrum area (SA) were calculated in the frequency domain with Fourier analysis.